If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = -2x + -2 Reorder the terms: 2 + 3x = -2x + -2 Reorder the terms: 2 + 3x = -2 + -2x Solving 2 + 3x = -2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + 3x + 2x = -2 + -2x + 2x Combine like terms: 3x + 2x = 5x 2 + 5x = -2 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + 5x = -2 + 0 2 + 5x = -2 Add '-2' to each side of the equation. 2 + -2 + 5x = -2 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = -2 + -2 5x = -2 + -2 Combine like terms: -2 + -2 = -4 5x = -4 Divide each side by '5'. x = -0.8 Simplifying x = -0.8
| (f+6)squared=144 | | 42=3v+12 | | 3(x^2-2x-8)=0 | | 6x-2y=-30 | | 5+x=2x-3-8 | | 3(x-6)=6(x-3) | | 360=x+(9x-35)+(x-46)+.5x | | 2x-19=(-5)x+9 | | 2u-11=5(u+2) | | x-7=4x+1 | | 8x+18=3x+-7 | | 6x+1=4x-13 | | (x-15)-(2x-13)=1 | | 6x(6x)+5(3x(3x)-x)-3x= | | 4x-3+90=180 | | f(x)=500-75x | | 3x(x-2)=24 | | 3x(x-2)=23 | | (1+0.05)4= | | A=0.5(b+12)5 | | 2x-6+2x-9=180 | | 9+x+7+x=50 | | 2-3(x-5)=20 | | 23x=10x+5 | | 4-y=230 | | 4x=18+4 | | 10x=5x+2 | | 5(3)=3645 | | (11x*2/3)*(11x*-2/3) | | 19-a=-2a | | 2x-27=95 | | 10-6x=20-26x |